Use of project-based learning in increasing students' vocabulary knowledge & communicative ability - Shafaei, Azadeh; Poorverdi, Mona; Parvizi, Behnaz (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
The paper reports on a study that examined the use of Project-Based Learning (PBL) increasing students’ vocabulary knowledge. The study was conducted in some private institutes for some Iranian junior high school students.After applying the approach and conducting post-test, significant differences were observed. This approach can be used as a training tool to help acquire vocabulary. The Project-Based Learning (PBL) approach in education often generates justifiable enthusiasm among those who have become frustrated with the limitations of traditional lecture-based education. In recent years, it has been widely acknowledged that classes designed by utilizing Project-Based Learning (PBL) are effective in enhancing the problem-solving ability of students.In PBL-based classes, students worked in groups and tried to apply their knowledge to solve the problems by themselves; therefore, such classes were effective in improving students’ vocabulary knowledge and communication abilities.